Pengaruh kepribadian terhadap bias perilaku investor individual di Indonesia dengan mediasi motivasi sosial - Santoso, Sidi; Arifin, Agus Zainul (Universitas Tarumanagara, 2024)
This research aims to examine the relationship between the five-factor model of personality and behavioral biases among individual investors in Indonesia when making stock investment decisions, mediated by social motivation. After testing the questionnaire’s feasibility and validity, it was distributed to 500 respondents to collect responses. The researchers conducted multiple regression analyses using the SmartPLS 4.0 tool to identify the relationship between the five-factor model of personality and behavioral biases among individual stock investors. Our findings revealed a high level of extroversion and a low level of neuroticism among stock investors in Indonesia, indicating significant relationships with investor biases in Indonesia, specifically the deposition effect and herding. However, the mediation used, in the form of social motivation, did not prove to have a significant influence as a mediator between the five-factor model of personality and investor behavioral biases. The limitations of this study include the possibility of analyzing primary and secondary investor data from both national and international stock brokerage firms, as well as the use of a larger sample to achieve findings that better represent the general conditions. This study represents the first comprehensive research exploring the relationship between personality traits, social motivation, and behavioral biases among individual stock investors in Indonesia. Furthermore, it provides valuable insights for a deeper understanding of the factors influencing stock investment decisions. Tujuan dari penelitian ini adalah untuk menguji hubungan antara kepribadian model lima faktor dan bias perilaku para investor individual di Indonesia pada saat membuat keputusan berinvestasi saham yang dimediasikan oleh motivasi sosial. Setelah menguji kelayakan dan validitas kuesioner, kuesioner tersebut disebarkan ke 500 responden untuk mendapatkan respons. Peneliti melakukan analisis regresi berganda menggunakan alat bantu SmartPLS 4.0 untuk mengidentifikasi hubungan antara model lima faktor kepribadian dan bias perilaku di kalangan para investor saham individual. Temuan kami mengungkap tingkat tinggi ekstrover serta tingkat rendah neurotisme di antara para investor saham di Indonesia menunjukkan hubungan yang signifikan terhadap bias perilaku investor di Indonesia, yaitu bias deposition effect dan herding. Akan tetapi, mediasi yang digunakan berupa motivasi sosial tidak terbukti berpengaruh signifikan sebagai mediasi antara model lima faktor kepribadian terhadap bias perilaku investor. Batasan penelitian ini meliputi kemungkinan analisis data investor primer dan sekunder dari perusahaan pialang saham baik nasional ataupun internasional, serta penggunaan sampel yang lebih besar untuk temuan yang bisa lebih mewakili kondisi umum. Studi ini menjadi penelitian komprehensif pertama yang mengeksplorasi hubungan antara sifat kepribadian, motivasi sosial, dan bias perilaku di kalangan para investor saham individual di Indonesia, selain itu memberikan wawasan yang berharga bagi pemahaman lebih lanjut tentang faktor-faktor yang memengaruhi keputusan investasi saham.